The Influence of Predictors on Work-Life Balance Among Oil and Gas Employees in Malaysia - Nurul Aida, Salah Pikri (2024)
In today's fast-paced world, achieving a harmonious balance between work responsibilities and personal life is a pressing concern, particularly in industries characterized by demanding work schedules and high levels of stress, such as the oil and gas sector. This study aims to explore the dynamics of work-life balance among employees in the oil and gas industry in Malaysia, examining the factors influencing their ability to effectively manage work-related obligations alongside personal and family commitments. Through a quantitative method approach, data collected from various organizational levels in oil and gas company in Malaysia. This reveals the prevalence of work-related stressors and their impact on employees' perceived work-life balance, and provide a deeper understanding of individual experiences, coping strategies, and organizational support systems. Findings suggest that factors such as time management, family commitment, and supervisory support towards pose significant challenges to achieving worklife balance in the oil and gas sector. Moreover, time management, familial, and supervisory support emerged as crucial buffers against work-related stress, highlighting the importance of organizational policies and practices that facilitate flexible work arrangements and promote employee well-being. This research contributes to existing literature by shedding light on the nuanced complexities of work-life balance within the context of the oil and gas industry, offering practical implications for organizational leaders, policymakers, and human resource practitioners striving to enhance employee satisfaction, retention, and overall productivity in this demanding work environment.